La famille substitut, la loi et la pratique en service social - Deleury, Édith; Rivet, Michèle (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1982)
The surrogate family is a key element in the government's efforts to publicize social services in Quebec and to make them a matter of collective responsability. The following article reviews laws and practices related to the existence and use of the surrogate family over the past years.